Use of Benzodiazepines in Primary Health Care - Camargo, Beatriz Milene de Oliveira; Pereira, Karina de Lima Andrade; Greco Filho, José Eduardo Paes de Barros; Silva, Fernanda Maria Bom da; Castellani, Cintia (Revista de Medicina, 2023)
According to the Brazilian Guideline on Psychiatry, roughly 50% of individuals who take benzodiazepines in a 1-year period are at risk of withdrawal syndrome, in addition to reduced capacity to work and greater expenses to the health care system. That said, the present study has been set to assess the prescription of these pharmaceuticals in the primary health service unit called “Alto da Riviera” in São Paulo, Brazil, with the purpose of raising the awareness about the abusive use of these drugs. The data were collected between 28th of March to 1st of April in 2022, including the following information: dosage form, month in which the medication was collected, patient identification (name and gender) and prescribed amount. After data analysis utilizing SWOT and Maguerez’s Arch, we were able to identify strengths and shortcomings regarding the health care system. The data compilation allowed us to realize that 64.9% of prescriptions were for clonazepam, being the dosage of 2 and 0,5 mg the most common. At this time, more than 30% of the patients had one or two prescription renewals. Therefore, it becomes clear the significance of the elaboration and the use of protocols and awareness programs for patients and prescriber, as well as present the hazards of the prescription drug abuse and its challenges in the primary health care settings.